Studi Penambatan Molekul Senyawa Turunan Kurkuminoid Terhadap Enzim Penicillin Binding Protein 2A Pada Bakteri MRSA - Mulki Irpani, Abdul; Indra Dinata, Deden (Universitas Bhakti Kencana, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is a bacterium that is resistant to ?-lactam antibiotics such as methicillins, a clinical problem that continues to affect the entire world. Resistance occurs as a result of the structural modification of Penicillin Binding Protein Penicilin Binding (PBP) MRSA. An organic active compound with antibacterial properties has sparked public interest, one of which is curcumin, which is known to have powerful antibacteric potential and can damage bacterial membranes. The aim of this study is to identify a compound of curcuminoid derivatives that could potentially be an antibacterial drug candidate for MRSA with in silico studies using molecular docking methods. The results obtained curcumin compounds have a free-binding energy of -5,56 kcal/mol, de-methoxy curcumine -6,25 kcal /mol and bis-demethoxy curcumin -6,24 kkal /mol. The interactions formed indicate the affinity of binding, from the data obtained all ligans possess good affinities even though the value of free-binding energy is lower than natural ligans.